2019
DOI: 10.4314/ahs.v19i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and victimization of students: a case study of a higher education institution in South Africa

Abstract: Introduction Sexual harassment has been identified as a major public health problem that is hidden in most institutions/organizations. Objective This study assessed sexual harassment and victimization of students in a higher institution in South Africa. Methods A quantitative, cross-sectional descriptive design was used in this study. The target population was registered students of the higher education institution and the sample size was 342… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…Few of the respondents further confirms that they have been sexually harassed in exchange for good grade in the past. The finding also supports the views from researches that opined sex in exchange for grades are found in tertiary institutions of Nigeria (Oni, Tshitangano, & Akinsola, 2019;Dastile, 2004). Consistent with previous studies (Sharma, 2013;Olaleye, & Ajuwon, 2012;Bastiani, Romito, & Saurel-Cubizolles, 2018;Ogunbameru, 2006;Effa, Okokon, Nwagbara, & Bello, 2012;Kullima et al, 2010), the results of this study revealed the common forms of sexual harassment experienced by the students.…”
Section: Discussionsupporting
confidence: 88%
“…Few of the respondents further confirms that they have been sexually harassed in exchange for good grade in the past. The finding also supports the views from researches that opined sex in exchange for grades are found in tertiary institutions of Nigeria (Oni, Tshitangano, & Akinsola, 2019;Dastile, 2004). Consistent with previous studies (Sharma, 2013;Olaleye, & Ajuwon, 2012;Bastiani, Romito, & Saurel-Cubizolles, 2018;Ogunbameru, 2006;Effa, Okokon, Nwagbara, & Bello, 2012;Kullima et al, 2010), the results of this study revealed the common forms of sexual harassment experienced by the students.…”
Section: Discussionsupporting
confidence: 88%
“…Influential commentaries and reviews [2,3] stress the urgency of closing Africa's gender gaps in STEM, and there is an emerging rigorous qualitative literature, e.g., [12,[18][19][20][21]. However, we know of only two quantitative studies on women's participation in STEM in SSA [14,22]; both are descriptive rather than inferential. A second important contribution of our study is the set of evidence-based interventions we present that universities and other institutions could adopt to enhance women's participation in PhD programs in STEM fields in SSA.…”
Section: Plos Onementioning
confidence: 99%
“…A complex interaction of many factors explains women's underrepresentation in science and technology fields, with the STEM pipeline "leaking" girls and women at various stages from secondary school through undergraduate and graduate studies and as they transition to a career in STEM [4,[10][11][12][13][14][15][16]. The present study focuses on the PhD portion of the STEM pipeline and examines whether there are gender-based differences in PhD performance (e.g., number of publications) and completion for students in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that different forms of sexual harassment against women include the following: inappropriate sexual comments, unwanted touching of female students' breasts, tapping of the female students' buttocks, and enticing of female students with high scores for sex (Onoyase, 2019). Similarly, Oni et al (2019) observed that: unwanted touching, unwanted fondling, unwanted sexual advance, sex-related jokes, sex-related insults, unwanted sexual gestures and unwanted sexual oriented text messages, letters and phone calls are forms of sexual harassment against female folks.…”
Section: Review Human Sexuality and Sexual Harassmentmentioning
confidence: 99%